Instrumenting Scenarios in a Model-Driven Development Environment - Grieskamp, Wolfgang; Tillmann, Nikolai; Veanes, Margus (Journal of Information and Software Technology, 2004)
SpecExplorer is an integrated environment for modeldriven development of .NET software. In this paper we discuss how scenarios can be described in SpecExplorer’s modeling language, Spec#, and how the SpecExplorer tool can be used to validate those scenarios by various means.